2019
DOI: 10.48550/arxiv.1902.06616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Some non-abelian covers of knots with non-trivial Alexander polynomial

Abstract: Let K be a tame knot embedded in S 3 . We address the problem of finding the minimal degree non-cyclic cover p : X → S 3 K. When K has non-trivial Alexander polynomial we construct finite non-abelian representations ρ : π1 S 3 K → G, and provide bounds for the order of G in terms of the crossing number of K which is an improvement on a result of Broaddus in this case. Using classical covering space theory along with the theory of Alexander stratifications we establish an upper and lower bound for the first bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Assuming the generalized Riemann hypothesis, Kuperberg showed that for every non-trivial knot K, some non-abelian quotient of S 3 K is bounded in size by a function of the form exp(poly(c(K))), implying that unknot recognition is in the complexity class co-NP [23]. See also Broaddus [9] and Morris [30] for other constructions of non-abelian covers.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the generalized Riemann hypothesis, Kuperberg showed that for every non-trivial knot K, some non-abelian quotient of S 3 K is bounded in size by a function of the form exp(poly(c(K))), implying that unknot recognition is in the complexity class co-NP [23]. See also Broaddus [9] and Morris [30] for other constructions of non-abelian covers.…”
Section: Introductionmentioning
confidence: 99%